Value co-creation in public procurement processes : A qualitative study of the recreational boatyard industry service ecosystem in Finland - Lindgren, Joonas (My University, 2021)
This study explores through the theoretical lens of value co-creation how value can emerge between actors in public procurement processes in the context of recreational boatyards service ecosystems in Finland. The motivation of this study is to find out why SMEs’ participation in public procurements is not improving despite interventions and examine how value can be co-created in the public procurement processes. The research attempts to do this by presenting the different perceptions of value, the institutional factors that are influencing the value creation process and the co-creation practices present in the context. The theoretical background of the study consists of literature relating to the concepts of value, value co-creation, service ecosystems and public procurement processes. This study utilizes a qualitative research approach with critical realism as research philosophy that allows retroduction of institutionalized explanation from the context of study. To reveal the context of study, secondary data in the form of procurement documents, practitioner’s literature and law text are used. The empirical research conducted for this study is based on data from semi-structured interviews collected. A total of 7 interviews were conducted between March to April 2021. The interviewees consist of representatives from SMEs service providers and public organizations from the context of study. The results suggest that although principles of the law oblige procurement conduct-ing actors, there is room for interpretation of what is “most economically advantageous” in the organizational context. Competence and personal beliefs of the procurement conducting actor is found to have influence on the tender evaluation. While the tendering period is heavily restricted by the law, unrestricted value co-creation is possible prior to the preparation of the procurement documents and in contractual period in the boundaries of contractual terms. Trust and relationships, facilitated by communication, were found to emerge from value co-creation practices. The findings of this study contribute to the body of knowledge in value co-creation and service ecosystems theories by revealing power structures between service ecosystems and value co-creation practices. The practical contribution of this research is to provide information for SMEs on contract awarding and to reveal shortcomings of current public procurement policies. It aims to assist SMEs to adapt their business model and value proposal to suit the context of future public procurements.

Tämä tutkimus käsittelee arvon yhteisluonnin näkökulmasta arvon muodostumista julkisissa hankinnoissa. Tutkimuksen tarkoitus on löytää syitä, miksi PK-yritysten osallistuminen julkisiin hankintoihin ei ole kasvanut hankintalain ja -käytäntöjen muutoksista huolimatta. Syiden selvittämiseksi julkisten hankintojen arvon yhteisluontia tarkastellaan huvivenealan PK-yritysten kontekstissa: miten arvo käsitetään ja mitkä institutionaaliset tekijät vaikuttavat arvon luontiin ja yhteisluonnin käytäntöihin? Tutkimuksen teoreettinen viitekehys koostuu arvon luonnetta ja yhteisluontia sekä palveluekosysteemejä ja julkisten hankintojen prosesseja käsittelevästä tutkimuskirjallisuudesta. Tutkimus toteutettiin laadullisena tapaustutkimuksena, hyödyntäen kriittisen realismin menetelmin ensisijaisena aineistona puolijäsenneltyjä haastatteluja sekä toissijaisina aineistoina hankinta-asiakirjoja, ammattikirjallisuutta ja lakia julkisista hankinnoista. Seitsemän puolijäsenneltyä julkisten organisaatioiden ja PK-kokoisten palvelun-tarjoajien haastattelua toteutettiin maaliskuussa ja huhtikuussa 2021. Tutkimuksen tulokset osoittavat, että tulkinta kokonaisedullisimmasta tarjouksesta riippuu lain periaatteista huolimatta hankintaorganisaation kontekstista. Hankinnan suorittajan pätevyys ja uskomukset vaikuttavat tarjousten arviointiin. Koska laki säätelee tarkasti tarjousvaiheen menettelyitä, arvon yhteisluonti tapahtuu kahdessa vaiheessa, sekä ennen hankinta-asiakirjojen valmistelua että sopimuksen solmimisen jälkeen. Toimiva kommunikaatio mahdollistaa arvon yhteisluonnin käytännöt, jotka puolestaan vahvistavat luottamusta ja luovat onnistuessaan perustan liikesuhteelle. Tutkimuksen tulokset lisäävät teoreettista ymmärrystä arvon yhteisluonnin käytännöistä ja voimarakenteiden luonteesta julkisten hankintojen ympärille rakentuvissa palveluekosysteemeissä. Käytännön tasolla tutkimus tuottaa PK-yrityksille tietoutta hankintasopimusten tekemisestä sekä julkisten hankintojen menettelytavoista ja niiden heikkouksista. Lisäksi tutkimus tarjoaa PK-yrityksille neuvoja, miten mukauttaa liiketoimintamalli yhteensopivaksi julkisten hankintojen kanssa.
Keywords: value, value co-creation, service ecosystems, public procurement process